Pengaruh Dimensi Livestreaming Terhadap Perilaku Gen Z Dalam Pembelian Online Secara Kompulsif dan Niatan Membeli Secara Online - Baswara, Satsya Yoga; Widhiastuti, Ratieh; Amaliyah, Dhifah (Business and Accounting Education Journal, 2024)
In the current development of the digital world, a relatively new online marketing dimension has arisen called Livestreaming, although it is still quite new, as a marketing channel, livestreaming itself turns out to generate a lot of business opportunities in the world of e-commerce and social commerce. The existence of live streaming is also suspected to have a close relationship with the behavior patterns of the current generation z who spend a lot of time both at leisure and when working using various electronic media. This article aims to empirically investigate the extent to which the dimensions of livestreaming influence the Z gene, affecting the cognitive and emotional reactions of its users and whether it will ultimately affect the consumption behavior of these online users and what effect it has on purchase intentions. The research method is to use an online questionnaire. And the tools we were used is warp PLS. The result are, livestreaming dimensions have positive effect on two kind of behavior that we research in this paper, such as information task fit and visual effect. although using livestreaming as a media to promoting goods in online marketplace in indonesia case still a new things and could bring some harmful inheritance effect. Keywords: livestreaming dimensions, gen z, electronic social commerce